2021
DOI: 10.1097/rli.0000000000000791
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automatic Deep Learning in Bi-institutional Prostate Magnetic Resonance Imaging

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…Therefore, we put more data in the testing set (69 csPCa, 71 non-csPCa cases) to better evaluate and verify the generalization ability of the model. Our proposed biparametric model yielded high sensitivity of 98.6% for csPCa detection based on patients, as well as other studies with the sensitivity ranging from 82.9% to 97% ( 13 , 14 , 39 41 ). However, it is worth noting that the specificity was not as high as expected in our study (64.8%) and in other studies (47%–76%) ( 12 14 , 39 ).…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, we put more data in the testing set (69 csPCa, 71 non-csPCa cases) to better evaluate and verify the generalization ability of the model. Our proposed biparametric model yielded high sensitivity of 98.6% for csPCa detection based on patients, as well as other studies with the sensitivity ranging from 82.9% to 97% ( 13 , 14 , 39 41 ). However, it is worth noting that the specificity was not as high as expected in our study (64.8%) and in other studies (47%–76%) ( 12 14 , 39 ).…”
Section: Discussionsupporting
confidence: 76%
“…Eight studies were included in the final selection [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. An overview of the selected studies is shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies (50%) used only two-dimensional (2D) operations within their model architecture, while two studies (25%) used three-dimensional (3D) operations. One study [ 23 ] used a combination of 2D and 3D architectures. One study used a 2.5 approach [ 25 ] by supplying two slices adjacent to the target slice as additional inputs to the model while using 2D operations within the model architecture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations